Biosorption of lead by cotton shells powder: Characterization and equilibrium modeling study. Issue 2 (28th January 2019) - Akram, Muhammad; Khan, Binish; Imran, Muhammad; Ahmad, Iftikhar; Ajaz, Humayun; Tahir, Muhammad; Rabbani, Faiz; Kaleem, Imdad; Nadeem Akhtar, Muhammad; Ahmad, Naveed; Samad Shah, Noor
Abstract: Lead (Pb) is a toxic heavy metal causing serious health risks to humans and animals. In the present study, cotton ( Gossypium hirsutum L.) shells powder was used as adsorbent for the treatment of synthetic Pb-contaminated water. The batch scale biosorption capacity of cotton shells powder was evaluated to study the effects of Pb concentrations, adsorbent doses and contact time at constant pH (6) and temperature (25 °C). Results revealed that sorption of Pb increased ( q = 0.09–9.60 mg/g) with increasing Pb concentration (1–15 mg/L) and contact time (15–90 min) while decreasing adsorbent dose (1–0.1 g/100 mL). The maximum Pb removal (90%) was achieved at Pb concentration (1 mg/L), contact time (90 min) and adsorbent dose (1 g/100 mL). Freundlich isotherm model proved best fit for Pb sorption ( R 2 = 0.99). The cotton shells powder has microporous structure confirmed by SEM, and has BET surface area (45 m 2 /g) and pore size (2.3 µm). These surface moieties along with various functional groups (C-H, C-O, C=O, O-H, S=O) confirmed by FTIR analysis might involve in Pb removal by complexation and ion exchange mechanisms. The cotton shells powder biomass could be considered as promising adsorbent for the removal of Pb from contaminated water.